2014
DOI: 10.1371/journal.pone.0086444
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Hospital and Surgeon Volume on Short-Term Survival after Hepatic Resection in a Population-Based Study

Abstract: BackgroundThe influence of different hospital and surgeon volumes on short-term survival after hepatic resection is not clearly clarified. By taking the known prognostic factors into account, the purpose of this study is to assess the combined effects of hospital and surgeon volume on short-term survival after hepatic resection.Methods13,159 patients who underwent hepatic resection between 2002 and 2006 were identified in the Taiwan National Health Insurance Research Database. Data were extracted from it and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Definitions of HVHs and LVHs performing hepatectomy varied between studies. Thresholds defining HVH in the abovementioned studies were 10–100 hepatectomies per year . A multiple logistic regression model showed that the cutoffs of high‐level HBP surgeries performed per year at hospitals that predicted 30‐day mortality and operative mortality after MOS hepatectomies were 10 and 50 in the present study.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Definitions of HVHs and LVHs performing hepatectomy varied between studies. Thresholds defining HVH in the abovementioned studies were 10–100 hepatectomies per year . A multiple logistic regression model showed that the cutoffs of high‐level HBP surgeries performed per year at hospitals that predicted 30‐day mortality and operative mortality after MOS hepatectomies were 10 and 50 in the present study.…”
Section: Discussionsupporting
confidence: 45%
“…According to the nationwide studies of hepatic surgery, the proportion of high‐volume hospitals (HVHs) among all hospitals and the proportion of cases performed at HVHs were 2.4–10% and 32–75%, respectively . In all these studies except one from the United States , which analyzed data covering approximately 20% of all discharges in the United States, the numbers of HVHs were small: 6–23 hospitals . It may be said that centralization of hepatic surgery in Japan has advanced to a certain degree, though the numbers of HVHs are limited, and centralization has advanced further in some countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed analysis of recurrence pattern and the treatment for recurrence would not have been possible using population-based data [12,14]. In addition, although population-based analyses are said to better describe the outcomes achieved in routine practice [14], the trend in centralization of high-risk surgery is associated with improved shortas well as long-term outcomes [32][33][34][35][36][37][38][39][40][41][42]. Considering much better outcomes reported from high-volume liver centers [20,[43][44][45], the results demonstrated in the current study may reflect ideal practice in the near future when centralization is optimized for older patients with CRLMs undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed analysis of recurrence pattern and the treatment for recurrence would not have been possible using population-based data [12,14]. In addition, although population-based analyses are said to better describe the outcomes achieved in routine practice [14], the trend in centralization of high-risk surgery is associated with improved short-as well as long-term outcomes [32][33][34][35][36][37][38][39][40][41][42]. Considering much better outcomes reported from high-volume liver centers [20,[43][44][45], the results demonstrated in the current study may re ect ideal practice in the near future when centralization is optimized for older patients with CRLMs undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%